Identification of Obstacle Students Physics Education FKIP USK in the Process of Online Learning - Ramiah Ramiah; Susanna Susanna; Abdul Hamid (Universitas Syiah Kuala, 2021)
The learning process is carried out face-to-face or at certain times as well as E-learning, but the outbreak of the Covid-19 virus has caused sudden changes causing student learning disruption due to having to adapt to the implementation of online learning. This study aims to identify the obstacles faced by Physics Education students of FKIP USK in the online learning process. The research subjects were 70 physics education students in class 2019. The method used is qualitative research with a descriptive design. Data collection was carried out by using a closed-based questionnaire google form. Data processing uses simple statistics in the form of percentage calculations. The results of the percentage data analysis showed that from the external aspect 62.9% experienced obstacles. From the results of the identification of obstacles faced by physics education students in the online learning process, The highest impact felt was the network followed by practicum and followed by a home atmosphere, which caused disruption to students in online learning.